KEABSAHAN KONTRAK YANG MENGGUNAKAN BAHASA ASING - Tunggono, Michael; Dwiyatmi , Sri Harini (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
Making an agreement basically contains rules to regulate an agreement that is valid and can be implemented so that it is not null and void by law. Decision Number 35/PDT.G/2010/Pn.Pra is a case of an agreement that occurred in only one (1) language, namely English. In this decision the judge gave the consideration that an agreement made only in English was a valid agreement because there was an agreement that the agreement was made only in English. In this research the author discusses the judge's considerations and the validity of contracts that only use one language, namely a foreign language. The judge's considerations in this decision were wrong because they did not refer to the legal terms of an agreement and violated Article 31 of Law Number 24 of 2009 which requires agreements to be made in Indonesian.